2003
DOI: 10.1213/01.ane.0000054001.37346.03
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Tranexamic Acid Reduces Postoperative Bleeding After Coronary Surgery in Patients Treated with Aspirin Until Surgery

Abstract: Continuation of aspirin medication until the day before coronary artery bypass grafting may increase postoperative bleeding. The administration of a single dose of tranexamic acid (30 mg/kg) immediately before cardiopulmonary bypass significantly reduced postoperative bleeding and inhibited fibrinolysis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 25 publications
1
52
0
5
Order By: Relevance
“…In line with the results of this research, a study by Pleym et al (20) in 2003 and a meta-analysis (21) in 2012 revealed that antifibrinolytic drugs such as aprotinin were effective in bleeding reduction during surgery.…”
Section: Discussionsupporting
confidence: 80%
“…In line with the results of this research, a study by Pleym et al (20) in 2003 and a meta-analysis (21) in 2012 revealed that antifibrinolytic drugs such as aprotinin were effective in bleeding reduction during surgery.…”
Section: Discussionsupporting
confidence: 80%
“…2 However, significant reductions in the number of patients transfused have been noted in patients who underwent various cardiac surgical procedures requiring cardiopulmonary bypass when lysine analogues were compared with placebo. [12][13][14][15][16][17] Reexploration for bleeding occurs in Ͻ5% of patients after cardiac surgery, but it usually is indicative of clinically significant surgical bleeding and is associated with an increase in operative mortality and morbidity. In 17 studies comparing high-dose aprotinin with control and 11 studies comparing TXA with control, aprotinin but not TXA was consistently associated with a significant reduction in the need for reexploration.…”
Section: Article P 2801mentioning
confidence: 99%
“…However, a study by Pleym et al (12) showed that TA given over 5 min immediately before the start of CPB reduces postoperative bleeding in first-time CABG patients. The ideal dosage of TA remains controversial.…”
Section: Discussionmentioning
confidence: 99%